Advances in the clinical management of dentin hypersensitivity: a review of recent evidence for the efficacy of dentifrices in providing instant and lasting relief - Cummins, D (The Journal of clinical dentistry, 2011)
This paper summarizes the current state of knowledge of the epidemiology, etiology, and clinical management of dentin hypersensitivity, with special emphasis on the evidence for the effectiveness of commonly available sensitivity relief toothpastes. It reviews the scientific and clinical research validating the effectiveness of a recently introduced toothpaste containing 8.0% arginine and calcium carbonate, known as Pro-Argin technology, including clinical evidence for the superior efficacy of this toothpaste versus potassium-based sensitivity relief toothpastes. It critiques recently published studies on a strontium-based sensitivity relief toothpaste. Finally, it summarizes new clinical data from three parallel, randomized, head-to-head studies comparing the efficacy of a toothpaste containing 8.0% arginine and calcium carbonate (positive control) to a strontium-based sensitivity relief toothpaste (test) in delivering superior instant and lasting sensitivity relief. The results of these new clinical studies clearly support the conclusions that 1) a toothpaste containing 8.0% arginine and calcium carbonate provides superior efficacy with respect to both immediate and lasting relief of dentin hypersensitivity compared to a toothpaste containing 8% strontium acetate, and 2) a toothpaste containing 8% strontium acetate is no more effective in providing immediate relief of dentin hypersensitivity than a regular fluoride toothpaste.